The evolutionary history of the hominin hand since the last common ancestor of Pan and Homo - Tocheri, Matthew W (Blackwell Science Inc, 2008)
Molecular evidence indicates that the last common ancestor of the genus Pan and the hominin clade existed between 8 and 4 million years ago (Ma). The current fossil record indicates the Pan-Homo last common ancestor existed at least 5 Ma and most likely between 6 and 7 Ma. Together, the molecular and fossil evidence has important consequences for interpreting the evolutionary history of the hand within the tribe Hominini (hominins). Firstly, parsimony supports the hypothesis that the hand of the last common ancestor most likely resembled that of an extant great ape overall (Pan, Gorilla, and Pongo), and that of an African ape in particular. Second, it provides a context for interpreting the derived changes to the hand that have evolved in various hominins. For example, the Australopithecus afarensis hand is likely derived in comparison with that of the Pan–Homo last common ancestor in having shorter fingers relative to thumb length and more proximo-distally oriented joints between its capitate, second metacarpal, and trapezium. This evidence suggests that these derived features evolved prior to the intensification of stone tool-related hominin behaviors beginning around 2.5 Ma. However, a majority of primitive features most likely present in the Pan-Homo last common ancestor are retained in the hands of Australopithecus, Paranthropus/early Homo, and Homo floresiensis. This evidence suggests that further derived changes to the hands of other hominins such as modern humans and Neandertals did not evolve until after 2.5 Ma and possibly even later than 1.5 Ma, which is currently the earliest evidence of Acheulian technology. The derived hands of modern humans and Neandertals may indicate a morphological commitment to tool-related manipulative behaviors beyond that observed in other hominins, including those (e.g. H. floresiensis) which may be descended from earlier tool-making species.